EFEKTIVITAS MANAJEMEN KEPEMIMPINAN PENDIDIKAN DALAM KOPERASI SEKOLAH SEBAGAI UPAYA MENDUKUNG PEMBELAJARAN EKONOMI SISWA DI MADRASAH (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the effectiveness of educational leadership management in school cooperatives as an effort to support economics learning for students at Madrasah. Grounded in the concept of educational leadership that is visionary, adaptive, and values-based (Siswadi, 2025; Siswadi, 2024), the study employs a descriptive qualitative approach through a systematic literature review of school cooperative management in Islamic educational institutions. The findings indicate that educational leadership plays a central role in driving cooperative management effectiveness, creating a contextual economic learning environment that integrates theory and practice. Through cooperative activities directed by a values-based leadership approach (Siswadi, Jamil, & Afandi, 2026), Madrasah students are able to understand economic concepts such as production, distribution, consumption, supply, and demand in a more concrete manner. Furthermore, students’ involvement in cooperative management has been proven to enhance managerial skills, including planning, organizing, actuating, and controlling, as well as to develop adaptive, participatory, and responsible leadership abilities. School cooperatives also contribute to fostering character values such as discipline, honesty, and teamwork, while simultaneously promoting students’ entrepreneurial spirit. However, implementation still faces challenges including suboptimal leadership, low student participation, and limited curriculum integration. Overall, effective educational leadership in Madrasah school cooperatives is proven to support practice-based economics learning while developing 21st-century competencies relevant to students’ future careers.